2020
DOI: 10.1177/2374373520919210
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Telephone Follow-Up on Patient Satisfaction in a Pediatric Neurosurgery Clinic

Abstract: Patient satisfaction is a key metric used to measure quality in health care. However, patient satisfaction measures in the pediatric population are less studied and understood than in the adult population. The purpose of this study was to evaluate the impact of telephone follow-up on patient satisfaction in an outpatient pediatric neurosurgery clinic. A standardized telephone follow-up call was performed within 1 week of a child’s clinic visit. Pearson’s χ2 or Fisher’s exact tests were used to assess changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Patient satisfaction is an important indicator of the quality and efficiency of health services and it is also one of the most important factors that determine success of a health institution (Manzoor et al, 2019). However, measurements of patient satisfaction in pediatric population have been less studied and understood compared to adult population (Blanco et al, 2020). With regard to this, it is necessary to determine the factors that affect patient satisfaction, expectations, and quality of care, especially in pediatric patients (Espinel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Patient satisfaction is an important indicator of the quality and efficiency of health services and it is also one of the most important factors that determine success of a health institution (Manzoor et al, 2019). However, measurements of patient satisfaction in pediatric population have been less studied and understood compared to adult population (Blanco et al, 2020). With regard to this, it is necessary to determine the factors that affect patient satisfaction, expectations, and quality of care, especially in pediatric patients (Espinel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…13 No matter how we follow up the patient’s treatment, such low-cost and convenient methods as leading the patient to the care-giving centers, home visits by the care providers, and use of telecommunication media are preferred. 14 Meanwhile, managing the outcomes of surgical procedures is a necessity. In a retrospective cohort study on healthy patients aged 0-18 years, it was reported that more than one-half of the patients needed consultation after surgery.…”
Section: Introductionmentioning
confidence: 99%